G24(P) Enhancing situational awareness through safety huddles – a staff perspective. (24th May 2017) - Venkataraman, A; Conn, R; Cotton, R; Abraham, S; Banaghan, M; Callaghan, B
Abstract : Introduction: Evidence from the literature shows that safety 'HUDDLES' (Healthcare Utilising Deliberate Discussion Linking Events) can enhance inter-professional relationships through improved communication, and consequently increase situational awareness among health care professionals. However, very few studies have explored staff perception of these huddles. Our aim was to assess the perspective of front line staff on the impact of daily safety huddles and explore further strategies to improve their delivery, enhancing situational awareness to improve patient safety. Methods: Safety huddles were implemented on two inpatient wards of a tertiary children's hospital (Great Ormond Street Hospital, London, UK). A staff survey was conducted at two time points post initiation of the huddles (18 months and 30 months) to evaluate the understanding of staff regarding these huddles. A questionnaire was devised and scored via Likert scales and free text responses. Results: Staff felt that safety huddles played a crucial part in highlighting patient problems and identifying clinical deterioration on the inpatient wards. It also improved communication among the team reducing anxiety and enhanced team cohesiveness Conclusion: Safety huddles had an extremely positive influence on front line staff. It can be easily implemented in health care setting and may increase situational awareness. Considering its positive impact, safety huddles have been introduced to other wards and specialities across the hospital. Huddles have also been included in the RCPCH S.A.F.E programme as one of the most important and core interventions to improve situational awareness.